Pergeseran Persepsi Budaya oleh Eksistensi Bahasa Indonesia pada Mahasiswa di Korea Selatan (2020-2024) - Pricilia Febriliani Worotikan; Jessica Natania Elvisnanda; Desiree Junike Angelica (Lembaga Pengembangan Kinerja Dosen, 2024)
As time progresses, language has become one of the diplomatic tools used in the international arena. In South Korea, interest in the Indonesian language has been growing, as evidenced by the increasing number of students showing interest in learning it each year. The author identifies an urgency to monitor the perceptions formed when foreign nationals learn Indonesian—in this context, South Korean society. This research seeks to elaborate on the cultural perceptions that emerge with the presence of the Indonesian language in South Korea. The aim of this study is to understand how the construction of cultural perceptions takes shape in the minds of South Koreans when they learn Indonesian. A descriptive qualitative research method was used, with data collection techniques in the form of interviews. The findings of this study indicate a shift in cultural perceptions of Indonesia, with Indonesian language learning fostering curiosity about Indonesian culture. Ultimately, this indirectly plays a role in promoting Indonesian culture. This shift is evident both in the mindset and in social interactions within the student community learning Indonesian.